Engaging vs. Non-Engaging Abutments: An In Vitro Study Evaluating Changes in Microgap and Screw Morphology - Fawaz M. Alzoubi; Mohammad Y. Sabti; Esra Alsarraf; Faris A. Alshahrani; Steven J. Sadowsky (MDPI AG, 2024)
Background: The purpose of this study was to compare the microgap size between engaging (E) and non-engaging (NE) abutments and screw morphology changes between E and NE abutments using scanning electron microscopy (SEM) before and after cyclic loading (CL). Methods: Thirty-six implants were arranged into four groups as follows: Group 1, single units with E abutments; Group 2, single units with NE abutments; Group 3, three-unit fixed partial dentures with a hemi-engaging design; and Group 4, three-unit FPDs with two NE abutments. The microgap was evaluated using a stereomicroscope. SEM was used to qualitatively evaluate screw morphology. The specimens were subjected to axial loading first and then lateral loading (30°) using the settings; one million cycles (1.0 × 106 cycles) for each loading axis. Results: There were no significant differences detected in the microgap sizes between the E and NE abutment groups. In addition, there were no significant changes in the microgap sizes after CL in the E or NE abutment specimens. More damage to the screws was noticed after CL compared to before, with no difference in the patterns of damage detected between the E and NE abutments. Conclusions: No significant difference in microgap size was detected between the E and NE abutments. Furthermore, there was no significant difference in microgap size between the different prosthetic designs. From the SEM qualitative evaluation, there were similar screw morphology changes after CL between the E and NE abutments.